Synthesis of Highly Functionalized 4‐Aminoquinolines. Issue 11 (16th February 2016) - Wezeman, Tim; Zhong, Sabilla; Nieger, Martin; Bräse, Stefan
Abstract: A diverse set of highly substituted 4‐aminoquinolines was synthesized from ynamides, triflic anhydride, 2‐chloropyridine, and readily accessible amides in a mild one‐step procedure. Abstract : Diverse products : Electrophilically activated amides easily react with sulfonyl ynamides to yield a diverse range of substituted 4‐aminoquinolines. The ynamides can be easily modified by Sonogashira processes or generated from dichloroenamide precursors. Any substituent can thus be introduced at the C3 position of the quinoline. 2‐ClPy=2‐chloropyridine, Tf2 O=triflic anhydride.